اکیسویں صدی کے اردو افسانے میں ملتان کی نمائندگی: ایک تنقیدی مطالعہ: “REPRESENTATION OF IN THE URDU AFSANA OF THE 21ST CENTURY: A CRITICAL STUDY’’ (Contemporary Journal of Social Science Review, 2025)
During the 21st century, compared to other literary centers of Urdu Afsana, Multan has witnessed the emergence of several remarkable Afsana writers who established a distinct literary identity for the region. Writers such as Dr. Liaqat Ali, Sahir Shafiq, and Nayyir Mustafa etc not only enriched Multan’s literary tradition but also aligned Urdu Afsana with new trends and possibilities. Their stories vividly reflect sociological, psychological, and abstract schools of thought. They transformed fiction from mere storytelling into an intellectual experience that explores human existence, social identity, and the individual’s relationship with a rapidly changing world.The 21st century Multani Afsana encompasses themes relevant to modern life, such as social disintegration, class disparity, and economic pressure, the decline of the family structure, environmental decay, women’s rights, and alienation. Through these subjects, the writers skillfully portray inner turmoil, loneliness, and crises of identity. The modern Multani Afsana thus becomes a mirror reflecting the confusion, emotional dislocation, and cultural fragmentation of contemporary life. Yet, it also embodies hope, romanticism, and regional spirit. Multan’s spiritual legacy and cultural sensitivity have given its fiction a unique aesthetic dimension, making it both locally rooted and universally human.